ACHIEVING STUDENTS 'DETAILED, THEORETICAL AND APPROACHED LEARNING IN THE TEACHING OF THE FIELD OF FINE ARTS AND IN THIS PROCESS THE TEACHER'S RESEARCH - Togayev Keldiyor Khamidovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article aims to provide students with a theoretical, practical and visual knowledge in the teaching of fine arts, and in this process the problem of the teacher's quest and the goals and objectives of the subject "Methods of Fine Arts", the stage of research and methods, the content and methodology of training, the content of extracurricular activities in educational institutions.